Prognostic Implications of Left Atrial Strain in Bicuspid Aortic Valve With Chronic Aortic Regurgitation - YuTing Tan; YuMan Li; WenHui Deng; RuiZe Zhang; RuoHan Zhao; Abudukadier Abulipizi; Jing Zhang; Xiang Ji; QuanFei Hou; Tianshu Liu; Lingyun Fang; Li Zhang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Left atrial reservoir strain (LARS) is a novel imaging biomarker of left ventricular diastolic dysfunction. This study aimed to examine the prognostic implications of LARS in patients with bicuspid aortic valve and significant (moderate‐severe to severe) aortic regurgitation. Methods and Results A total of 220 patients with bicuspid aortic valve and significant aortic regurgitation were prospectively enrolled in our study. LARS and left ventricular global longitudinal strain were derived from speckle‐tracking echocardiography. The end point was a composite of all‐cause mortality, heart failure hospitalization, and aortic valve repair or replacement. The threshold value of LARS <24% was used to identify impaired left atrial mechanics based on prior results. During a median follow‐up of 364 (interquartile range, 294–752) days, 46 patients (20.9%) reached the composite end points. On multivariable Cox analysis, impaired LARS (adjusted hazard ratio, 2.08 [95% CI, 1.05–4.11]; P=0.036) was a statistically significant predictor of composite end points after adjustment for other statistically significant predictors. Finally, adding impaired LARS to other statistically significant predictors (New York Heart Association functional class and left ventricular global longitudinal strain) significantly improved the global χ2 (from 32.19 to 36.56; P=0.037) and reclassification (continuous net reclassification index=0.55; P<0.001) of the prediction model. Conclusions In patients with bicuspid aortic valve and significant aortic regurgitation, the impairment of LARS is a strong independent prognostic predictor and confers incremental prognostic utility over clinical and other echocardiographic parameters. These findings suggest that LARS could be considered in risk stratification for such populations.